Sistem Informasi Pembelian, Persediaan, dan Penjualan untuk Apotek - Dewi, Lusiana Citra (ComTech: Computer, Mathematics and Engineering Applications, 2013)
This study aims to create a system that can simplify common operational activities of pharmacy such as purchasing, inventory, and sales. The system is expected to improve manual processes of purchasing, inventory, and sales into a computerized ones. In addition, this system also provides convenience, accuracy, and speed for owner or management to access reports of purchase, inventory, and sales in real-time. The research methods used are literature studies, field studies, and the methods of analysis and design of object-oriented information system design language UML (Unified Modeling Language). Tthe result of this research is an information system of purchasing, inventory, and sales of medicines that may help pharmacies to get information quickly and accurately, and to help pharmacy operations to run more effectively and efficiently.